2009
DOI: 10.1351/pac-con-08-08-31
|View full text |Cite
|
Sign up to set email alerts
|

The role of pyrimidine nucleobase excimers in DNA photophysics and photoreactivity

Abstract: Quantum chemical studies using the accurate CASPT2//CASSCF procedure show that π-stacked interactions in biochromophores such as pyrimidine (Pyr) DNA/RNA nucleobases pairs yield excimer-like situations which behave as precursors of processes like charge transfer (CT) or photoreactivity and are the source of the emissive properties in DNA. Examples are the CT between adjacent DNA nucleobases in a strand of oligonucleotides and the photodimerization taking place in cytosine (C) pairs leading to cyclobutanecytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…The repulsive states lead to crossing regions with the ground state at large R(O-O) distances. The corresponding conical intersections may mediate in this way an effective nonradiative decay channel towards the repopulation of the ground state, as it occurs in DNA/RNA nucleobases [48][49][50][51][52][53][54]. The well found on the 3 From an experimental standpoint, the wavelength of the emission peak ( max ) depends on the wavelength of the excitation applied ( exc ) in a variety of aqueous solutions employing different solutes (salts, Nafion 117 solution/film, L-lysine, D-alanine, D-glucose, and sucrose) [2].…”
Section: Fluorescence Spectroscopic Featuresmentioning
confidence: 99%
“…The repulsive states lead to crossing regions with the ground state at large R(O-O) distances. The corresponding conical intersections may mediate in this way an effective nonradiative decay channel towards the repopulation of the ground state, as it occurs in DNA/RNA nucleobases [48][49][50][51][52][53][54]. The well found on the 3 From an experimental standpoint, the wavelength of the emission peak ( max ) depends on the wavelength of the excitation applied ( exc ) in a variety of aqueous solutions employing different solutes (salts, Nafion 117 solution/film, L-lysine, D-alanine, D-glucose, and sucrose) [2].…”
Section: Fluorescence Spectroscopic Featuresmentioning
confidence: 99%
“…It has been shown in the studies on the excited state interactions of two nucleobases that the inclusion of dynamical correlation effects is necessary to correctly describe the chargetransfer as well as excimer states and, thus, the CASPT2 method has to be used for a reliable description of such systems. [29][30][31][32][33][34] It has been also shown that the basis set superposition error (BSSE) must be accounted for to properly characterize the potential energy surface of the excited state dimers and their stabilities. In these studies the states of pp* character were considered.…”
Section: Non-adiabatic Dynamicsmentioning
confidence: 99%